SAMe-TT2R2 predicts quality of anticoagulation in patients with acute venous thromboembolism: The MAQI2 experience. (June 2017) - Kataruka, Akash; Kong, Xiaowen; Haymart, Brian; Kline-Rogers, Eva; Almany, Steve; Kozlowski, Jay; Krol, Gregory D; Kaatz, Scott; McNamara, Michael W; Froehlich, James B; Barnes, Geoffrey D
A high SAMe-TT2 R2 score predicted poor warfarin control and adverse events among atrial fibrillation patients. However, the SAMe-TT2 R2 score has not been well validated in venous thromboembolism (VTE) patients. A cohort of 1943 warfarin-treated patients with acute VTE was analyzed to correlate the SAMe-TT2 R2 score with time in therapeutic range (TTR) and clinical adverse events. A TTR <60% was more frequent among patients with a high (>2) versus low (0–1) SAMe-TT2 R2 score (63.4% vs 52.3%, p <0.0001). A high SAMe-TT2 R2 score (>2) correlated with increased overall adverse events (7.9 vs 4.5 overall adverse events/100 patient years, p =0.002), driven primarily by increased recurrent VTE rates (4.2 vs 1.5 recurrent VTE/100 patient years, p =0.0003). The SAMe-TT2 R2 score had a modest predictive ability for international normalized ratio (INR) quality and adverse clinical events among warfarin-treated VTE patients. The utility of the SAMe-TT2 R2 score to guide clinical decision-making remains to be investigated.